Electrochemical investigation of 18k gold in acidic electrolyte - Grekulović Vesna J.; Rajčić-Vujasinović Mirjana M.; Stević Zoran M. (Hemijska Industrija, 2009)
The results of an attempt in using cyclic voltammetry for characterization of gold, silver, copper and 18-k gold alloys by their anodic behavior in 1 mol/dm3 H2SO4 are presented in this paper. Gold alloys containing 75 mass% Au are named as 18-k gold, but it is usually three component alloy containing 75 mass% Au, 12.5 mass% Ag and 12.5 mass% Cu as the main components. Investigated alloys were obtained by melting powders of pure metals mixed in corresponding ratio, casting, cooling in air, rolling and drawing in the wire shape. To achieve the required mechanical properties, the alloys had heat-treated three times. Each alloy exhibits characteristic current peaks on voltammogram that can be used to recognize the kind of present alloying metal in gold. Also, the content of the alloying metal can be roughly estimated from the peak value of current densities.